Information Literacy Skills and Online Learning: The Role of Academic Librarians as Information Facilitators - Akeriwe, Miriam Linda; Thompson, Edwin S. (Ghana Library Journal, 2016)
Information and Communication Technologies (ICTs) are changing education in many ways. ICTs are making learning more flexible and more personalized to meet individual needs. These technologies have brought about diverse ways of acquiring education, one such example is online learning. This has obviously impacted on the work of libraries since it has always been the responsibility of libraries to assist learners find. evaluate and effectively use information resources. It is in this vein that this paper explores what online learning entails and how the acquisition of information literacy skills could enhance the information - seeking processes of online learners. Again, to find out how these literacy skills could assist users effectively acquire the relevant information needed to enhance the successful completion of their online programmes. ICTs have evidently changed the role of librarians from the guardian to a navigator role. where they have to navigate their users through the complex maze of the digital information world. This paper therefore brings to light the role of librarians in all of this and how librarians can train users in acquiring information literacy skills to enable them effectively find and use information. Furthermore, the paper discusses how librarians could capitalize on their unique role as educators to efficiently educate their users to acquire these information literacy skills. The study, makes use of existing literature as well as researchers' personal experiences. The paper concludes with suggestions as to the way forward if libraries want to stay relevant.